Polylactic acid composite fiber membrane, preparation method and application thereof, and self-energized polylactic acid composite fiber membrane

By combining polylactic acid fibers with tetragonal barium titanate crystals, polylactic acid composite fiber membranes were prepared, solving the problems of dust filter materials being unable to intercept ultrafine dust and being non-degradable, thus achieving high-efficiency filtration and environmentally friendly effects.

CN119287582APending Publication Date: 2025-01-10SHENHUA SHENDONG COAL GRP +3
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411454884.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing dust filter materials are ineffective at intercepting ultrafine dust and are non-degradable, leading to environmental pollution.

Method used

A polylactic acid composite fiber membrane was prepared by electrospinning polylactic acid fiber and tetragonal barium titanate crystals. The tetragonal barium titanate crystals were embedded in the polylactic acid fiber to form a high-efficiency filter material.

Benefits of technology

It achieves efficient filtration of ultrafine dust, the material is biodegradable, reduces environmental pollution, and has good mechanical properties and electrostatic adsorption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287582A_ABST
    Figure CN119287582A_ABST
Patent Text Reader

Abstract

The invention provides a polylactic acid composite fiber membrane, a preparation method and application thereof and a self-powered polylactic acid composite fiber membrane, and relates to the technical field of dust control and fiber membrane materials. The polylactic acid composite fiber membrane comprises polylactic acid fibers and tetragonal-phase barium titanate crystals, the diameter of the polylactic acid fibers is 100-800 nm, the average particle size of the tetragonal-phase barium titanate crystals is 20-100 nm, and the tetragonal-phase barium titanate crystals are partially or completely embedded in the polylactic acid fibers. The polylactic acid composite fiber disclosed by the invention has good mechanical properties, stability and relatively high dielectric constant, and is suitable for being applied to preparation of materials capable of filtering fine particulate matters.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of dust prevention and control and fiber membrane materials, and in particular to a polylactic acid composite fiber membrane, a preparation method and application thereof, and a self-powered polylactic acid composite fiber membrane. Background Art

[0002] At present, many industries have the problem of high dust concentration at construction sites. For example, in the coal industry, the dust at the mining site is high, and disasters and accidents frequently occur during mine production. Another example is in the construction field, vehicles driving, mechanical handling and mixing at the construction site will generate a lot of dust. When workers work in an environment with high dust concentration for a long time, they will inhale a lot of dust into their bodies. The fine particles directly enter the human respiratory tract and alveoli, which can cause inflammation of the workers' respiratory system. Severe cases can turn into pneumoconiosis. Relevant data show that the mortality rate of pneumoconiosis is as high as 22%, and the number of deaths from coal mine pneumoconiosis is far greater than the number of deaths from coal mine production safety accidents.

[0003] Although there are dust control measures such as spray dust reduction and dust collector dust removal, they still cannot meet the needs of dust control, especially for ultrafine dust with a particle size of less than 2.5μm. The control effect is poor, and respirable dust with a particle size of less than 2.5μm can enter the alveolar area of ​​the human body and is the main cause of pneumoconiosis. Therefore, the development of filter materials that can effectively intercept ultrafine dust is of great significance to prevent the occurrence of pneumoconiosis and protect people's lives and health.

[0004] At present, most dust filtration materials use polypropylene fiber as the main material, which is turned into electrostatic electret meltblown cloth through electrostatic charging and other means, and used as the filter layer of protective masks. However, due to the non-degradability of polypropylene, it causes plastic pollution that cannot be ignored.

[0005] In view of this, it is necessary to provide a dust filtering material that is both biodegradable and has a good filtering effect. Summary of the invention

[0006] The main purpose of the present invention is to provide a polylactic acid composite fiber membrane, its preparation method and application, and a self-powered polylactic acid composite fiber membrane to solve the problems in the prior art that dust filter materials cannot be degraded, are easy to pollute the environment, and have low dust filtration efficiency.

[0007] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a polylactic acid composite fiber membrane is provided, wherein the polylactic acid composite fiber membrane comprises polylactic acid fibers and tetragonal barium titanate crystals, the average diameter of the polylactic acid fibers is 100nm-800nm, the average particle size of the tetragonal barium titanate crystals is 20nm-100nm, and the tetragonal barium titanate crystals are partially or completely embedded in the polylactic acid fibers.

[0008] Furthermore, the average diameter of the polylactic acid fibers is 300nm-500nm, and the average particle size of the tetragonal barium titanate crystals is 30nm-50nm.

[0009] Furthermore, the mass ratio of the polylactic acid fiber to the tetragonal barium titanate crystal is 1:5-2:1.

[0010] Furthermore, the mass ratio of the polylactic acid fiber to the tetragonal barium titanate crystal is 1:2-2:1.

[0011] In order to achieve the above object, according to another aspect of the present invention, a method for preparing the above polylactic acid composite fiber membrane is provided, comprising:

[0012] Step S1, preparing nano-barium titanate: adding a barium salt, a titanium-containing compound, and a first dispersant into water to obtain a first mixed solution, adjusting the pH value, and obtaining nano-barium titanate through a hydrothermal synthesis reaction;

[0013] Step S2, preparing tetragonal barium titanate crystals: calcining the nano-barium titanate to obtain tetragonal barium titanate crystals;

[0014] Step S3, preparing a polylactic acid composite fiber membrane: adding the tetragonal barium titanate crystals, polylactic acid and a second dispersant into a solvent to obtain a second mixed solution, obtaining a spinning solution, and preparing the polylactic acid composite fiber membrane by electrospinning.

[0015] Furthermore, in step S1, the barium salt is at least one of barium hydroxide, barium chloride and barium acetate.

[0016] Furthermore, the titanium-containing compound is at least one of titanium dioxide and titanium tetrachloride.

[0017] Furthermore, the first dispersant is at least one of polyvinyl pyrrolidone, carboxymethyl cellulose, and dopamine hydrochloride.

[0018] Furthermore, in the step of adjusting the pH value, the pH value of the first mixed solution is controlled to be 9-14; a pH adjuster is used to adjust the pH value, and the pH adjuster is at least one of potassium hydroxide, sodium hydroxide, and ammonia water.

[0019] Furthermore, based on the total mass of the first mixed liquid, the mass fraction of the barium salt is 3wt%-8wt%, the mass ratio of the titanium-containing compound to the barium salt is 1:2-2:1, the mass ratio of the first dispersant to the barium salt is 1:8-1:1, and the mass ratio of the pH adjuster to the barium salt is 1:6-2:1.

[0020] Furthermore, in step S3, the solvent is at least one of N,N-dimethylformamide, dichloromethane and chloroform.

[0021] Furthermore, in step S3, the second dispersant is at least one of polyvinyl pyrrolidone and dopamine hydrochloride.

[0022] Furthermore, based on the total mass of the second mixed liquid, the mass fraction of the polylactic acid is 5wt%-20wt%, the mass ratio of the tetragonal barium titanate crystals to the polylactic acid is 1:5-2:1, and the mass ratio of the second dispersant to the polylactic acid is 1:10-2:1.

[0023] Furthermore, in the step S1, the hydrothermal synthesis reaction is a microwave-assisted hydrothermal synthesis reaction; the temperature of the microwave-assisted hydrothermal synthesis reaction is 90°C-180°C, the time is 1h-5h, and the microwave power is 300W-1000W.

[0024] Furthermore, in the step S2, the calcination temperature is 800°C-1200°C, and the calcination time is 3h-8h; the purity of the tetragonal barium titanate crystals is 99.7%-99.9%, and the average particle size of the tetragonal barium titanate crystals is 20nm-100nm.

[0025] Furthermore, in step S3, the electrospinning conditions are: output voltage 15kV-50kV, solution consumption rate 0.5mL / h-1.5mL / h, fiber winding speed: 300rpm-2500rpm, spinning temperature 10℃-50℃, spinning distance 8cm-25cm.

[0026] According to another aspect of the present invention, there is provided an application of the above-mentioned polylactic acid composite fiber membrane in the field of preparing materials for filtering fine particulate matter.

[0027] In order to solve the above problems, according to another aspect of the present invention, a self-powered polylactic acid composite fiber membrane is provided, wherein the self-powered polylactic acid composite fiber membrane comprises the above polylactic acid composite fiber membrane and a metal mesh assembled on one or both sides of the polylactic acid composite fiber membrane.

[0028] Furthermore, the metal mesh is one of copper mesh, iron mesh, silver mesh, nickel mesh, titanium mesh, tungsten mesh, and molybdenum mesh; the pore size of the metal mesh is 50-300 mesh, the wire diameter is 0.03mm-0.15mm, and the thickness is 0.05mm-0.4mm.

[0029] By applying the technical solution of the present invention, a polylactic acid composite fiber membrane formed by combining degradable polylactic acid fibers and tetragonal barium titanate crystals with a high dielectric constant is environmentally friendly and has a very high dust filtration efficiency. In addition, in the polylactic acid composite fiber membrane of the present invention, the tetragonal barium titanate crystals are partially or completely embedded in the polylactic acid fibers, and the structure is stable, and fine particles can be filtered for a long time, thus solving the problem in the prior art that dust filtration materials are prone to plastic pollution and have low dust filtration efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The present invention is a flow chart of the preparation of the polylactic acid composite fiber membrane described in the embodiment;

[0031] Figure 2 This is a scanning electron microscope image of the tetragonal barium titanate crystal described in Example 1;

[0032] Figure 3 This is a scanning electron microscope image of the polylactic acid composite fiber membrane described in Example 2. DETAILED DESCRIPTION

[0033] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0034] As mentioned in the background technology of the present invention, there is a problem in the prior art that dust filter materials are difficult to degrade and easily cause plastic pollution. In order to solve the above problems, in a typical embodiment of the present invention, a polylactic acid composite fiber membrane is provided, the polylactic acid composite fiber membrane comprises polylactic acid fibers and tetragonal barium titanate crystals, the average diameter of the polylactic acid fibers is 100nm-800nm, the average particle size of the tetragonal barium titanate crystals is 20nm-100nm, and the tetragonal barium titanate crystals are partially or completely embedded in the polylactic acid fibers.

[0035] Polylactic acid is a biodegradable polymer that can be decomposed into carbon dioxide and water under natural conditions and is environmentally friendly. Polylactic acid can be produced by fermentation of plant-based materials such as corn and sugarcane and is renewable. It has good processability and can be formed through common plastic processing techniques such as blow molding, injection molding, and blister molding. It also has good corrosion resistance, biocompatibility, and mechanical stretchability, and has good application prospects.

[0036] Barium titanate has five crystal forms: hexagonal, cubic, trigonal, tetragonal, and orthorhombic. The tetragonal form has significant ferroelectricity, high dielectric constant, and piezoelectric effect, which enables it to effectively guarantee the high voltage output characteristics of polymer materials when dispersed in polymers as a piezoelectric phase. Since the helical structure in the polylactic acid molecular chain also exhibits shear piezoelectricity, mixed dispersion with tetragonal barium titanate crystals can improve the piezoelectric properties of polymer materials, better realize dipole polarization to generate voltage, and improve the electrostatic adsorption of dust by polylactic acid composite fiber membranes. The size of polylactic acid fibers and tetragonal barium titanate crystals will have a great influence on the mechanical properties of polylactic acid composite fiber membranes and the filtration efficiency of fine particles. The finer the size of the polylactic acid fiber, the better its shear piezoelectricity, but the mechanical properties such as breaking strength are low and not wear-resistant. Similarly, the size of tetragonal barium titanate crystals will also bring similar effects. The present invention can balance the mechanical properties of the polylactic acid composite fiber membrane and the fine particle filtration efficiency by controlling the diameter of the polylactic acid fiber and the size of the tetragonal barium titanate crystals within the above range, thereby improving its service life and expanding its application range. At the same time, unlike other composite methods, the present invention forms a composite fiber membrane by embedding tetragonal barium titanate crystals in polylactic acid fibers, which can prevent the tetragonal barium titanate crystals from falling off during use and reducing the long-term filtration performance of the polylactic acid composite fiber membrane.

[0037] In a preferred embodiment, the average diameter of the polylactic acid fiber is 300nm-500nm, and the average particle size of the tetragonal barium titanate crystal is 30nm-50nm. Adjusting the diameter of the polylactic acid fiber and the size of the tetragonal barium titanate crystal to the above range can further improve the comprehensive performance of the polylactic acid composite fiber membrane, so that it has higher breaking strength and filtration performance, has a lasting adsorption capacity for both PM2.5 and PM0.3, and has higher practicality.

[0038] In order to ensure a better fiberization effect and take into account the filtration efficiency of the polylactic acid composite fiber membrane, in a preferred embodiment, the mass ratio of the polylactic acid fiber to the tetragonal barium titanate crystal is 1:5-2:1. Controlling the mass ratio of the two within the above range is more conducive to avoiding the fiberization problem that may be caused by too high a proportion of tetragonal barium titanate crystals, and is also conducive to further improving the wear resistance and filtration efficiency of the polylactic acid composite fiber membrane.

[0039] In a preferred embodiment, the mass ratio of the polylactic acid fiber to the tetragonal barium titanate crystal is 1: 2-2: 1. Further limiting the mass ratio of the two can prepare a polylactic acid composite fiber membrane having both good breaking strength and filtration efficiency.

[0040] According to another aspect of the present invention, a method for preparing the above-mentioned polylactic acid composite fiber membrane is provided, the preparation method comprising:

[0041] Step S1, preparing nano-barium titanate: adding a barium salt, a titanium-containing compound, and a first dispersant into water to obtain a first mixed solution, adjusting the pH value, and obtaining nano-barium titanate through a hydrothermal synthesis reaction;

[0042] Step S2, preparing tetragonal barium titanate crystals: calcining the nano-barium titanate obtained in step S1 to obtain tetragonal barium titanate crystals;

[0043] Step S3, preparing a polylactic acid composite fiber membrane: adding the tetragonal barium titanate crystals obtained in step S2, polylactic acid and a second dispersant into a solvent to obtain a second mixed solution, obtaining a spinning solution, and preparing a polylactic acid composite fiber membrane by electrospinning.

[0044] Electrospinning technology is one of the simplest and most effective methods for preparing one-dimensional nanostructured materials. It has the advantages of simple equipment, controllable process parameters, fast preparation speed and low cost. Since the fiber membrane formed by electrospinning has the characteristics of small fiber diameter, many pores, small pore size and good fiber uniformity, it has received extensive attention and application in many fields. At the same time, it also shows great application potential in the fields of air filtration and personal protection.

[0045] The invention prepares nano-barium titanate in advance and then calcines it to obtain tetragonal barium titanate crystals with uniform particle size, and then mixes the nano-barium titanate with polylactic acid to prepare a polylactic acid composite fiber membrane by an electrostatic spinning method. The polylactic acid composite fiber membrane has good mechanical properties and certain filtration efficiency.

[0046] In step S1, the barium salt and the titanium-containing compound can be made of common barium titanate synthesis raw materials. For example, the barium salt includes but is not limited to at least one of barium hydroxide, barium chloride, and barium acetate, and the titanium-containing compound includes but is not limited to at least one of titanium dioxide and titanium tetrachloride.

[0047] The addition of the first dispersant is conducive to the dispersion of barium salts and titanium-containing compounds in water. In order to better exert the dispersing effect, in a preferred embodiment, the first dispersant includes but is not limited to at least one of polyvinyl pyrrolidone, carboxymethyl cellulose, and dopamine hydrochloride. Compared with other dispersants, the addition of the above-mentioned first dispersant can better prevent product aggregation, promote the progress of the hydrothermal reaction, and prepare nano-barium titanate with more uniform particle size and smaller size, laying a good foundation for the subsequent tetragonal phase barium titanate crystals to have more uniform and fine particle size, uniform distribution during the spinning process, and uniform intercalation in the fiber after molding. At the same time, the above-mentioned dispersant can also be decomposed during the subsequent calcination process to avoid the introduction of impurities.

[0048] During the hydrothermal synthesis reaction, a suitable pH environment is more conducive to the reaction. Preferably, by adjusting the pH value of the first mixed solution to 9-14, it is more conducive to the efficient and stable formation of nano-barium titanate. In the actual operation, a pH adjuster can be used to adjust the pH value, and the pH adjuster includes but is not limited to at least one of potassium hydroxide, sodium hydroxide, and ammonia water.

[0049] In a preferred embodiment, based on the total mass of the first mixed solution, the mass fraction of the barium salt is 3wt%-8wt%, the mass ratio of the titanium-containing compound to the barium salt is 1:2-2:1, the mass ratio of the first dispersant to the barium salt is 1:8-1:1, and the mass ratio of the pH regulator to the barium salt is 1:6-2:1. Controlling the amount of each component within the above range can improve the reaction efficiency without losing too much raw material, and the prepared nano barium titanate has good size uniformity.

[0050] In step S3, the solvent is a polylactic acid soluble material. Exemplarily, the solvent includes but is not limited to at least one of N,N-dimethylformamide, dichloromethane, and chloroform.

[0051] The addition of the second dispersant can improve the stability of the spinning solution and prevent the tetragonal barium titanate crystals from agglomerating and settling in the spinning solution. In a preferred embodiment, the second dispersant includes but is not limited to at least one of polyvinyl pyrrolidone and dopamine hydrochloride.

[0052] In a preferred embodiment, based on the total mass of the second mixed liquid, the mass fraction of polylactic acid is 5wt%-20wt%, the mass ratio of tetragonal barium titanate crystals to polylactic acid is 1:5-2:1, and the mass ratio of the second dispersant to polylactic acid is 1:10-2:1. The mass fraction of polylactic acid has a great influence on the diameter of polylactic acid fibers in the polylactic acid composite fiber film and the fiber-forming effect.

[0053] When the composition of the spinning solution and the ratio of each component meet the above limitations at the same time, the fibers prepared by electrospinning have uniform size, complete structure, certain mechanical properties and fine particle filtering performance.

[0054] In a preferred embodiment, the hydrothermal synthesis reaction is a microwave-assisted hydrothermal synthesis reaction; the temperature of the microwave-assisted hydrothermal synthesis reaction is 90°C-180°C, the time is 1h-5h, and the microwave power is 300W-1000W. Microwave-assisted hydrothermal synthesis reaction refers to a synthesis method that uses microwave radiation to accelerate the reaction rate and improve the product yield under hydrothermal conditions. In traditional hydrothermal synthesis, the reaction requires a long reaction time and high temperature, while microwave assistance can significantly shorten the reaction time and reduce the reaction temperature. The basic principle of microwave-assisted hydrothermal synthesis reaction is to use microwave radiation to heat the reaction system, increase the vibration, rotation and collision frequency of the reactant molecules, and thus accelerate the reaction rate. Microwave radiation can penetrate the medium and quickly transfer energy to the reactants, so that the reaction quickly reaches equilibrium, improves the reaction yield, has a short reaction time, mild reaction conditions, high product purity, and is easy to operate. In addition, the use of microwave-assisted hydrothermal synthesis reaction is also conducive to controlling the morphology of nano-barium titanate, making its particle size more uniform and fine.

[0055] In a preferred embodiment, in step S2, the calcination temperature is 800°C-1200°C, the calcination time is 3h-8h; the purity of the tetragonal barium titanate crystals is 99.7%-99.9%, and the average particle size of the tetragonal barium titanate crystals is 20nm-100nm. The tetragonal barium titanate crystals prepared by combining microwave-assisted hydrothermal synthesis reaction and calcination have good crystal form and high purity, which is beneficial to improving the dielectric properties of the polylactic acid composite fiber membrane and improving its filtration efficiency for fine particles.

[0056] In a preferred embodiment, in step S3, the electrospinning conditions are: output voltage 15kV-50kV, solution consumption rate 0.5mL / h-1.5mL / h, fiber winding speed: 300rpm-2500rpm, spinning temperature 10℃-50℃, spinning distance 8cm-25cm. The above-mentioned limitation on the electrospinning conditions can prepare fibers of the desired size, ensuring that the polylactic acid composite fiber membrane has both good mechanical properties and filtration properties.

[0057] According to another aspect of the present invention, there is provided an application of the above-mentioned polylactic acid composite fiber membrane in the field of preparing materials for filtering fine particulate matter, where the fine particulate matter is dust in the air, such as PM2.5.

[0058] According to another aspect of the present invention, a self-powered polylactic acid composite fiber membrane is provided, which comprises the above-mentioned polylactic acid composite fiber membrane or the polylactic acid composite fiber membrane prepared by the above-mentioned method, and a metal mesh assembled on one or both sides of the polylactic acid composite fiber membrane. Using the metal mesh as a charge output electrode, a self-powered long-term filtering material for fine particles can be prepared. The self-powered polylactic acid composite fiber membrane has a high surface potential, a high dielectric constant and a high electrostatic retention capacity, and has a good adsorption effect on fine particles PM2.5 or ultrafine particles PM0.3, and has excellent application prospects.

[0059] In a preferred embodiment, the metal mesh is one of copper mesh, iron mesh, silver mesh, nickel mesh, titanium mesh, tungsten mesh, and molybdenum mesh; the pore size of the metal mesh is 50-300 mesh, the wire diameter is 0.03mm-0.15mm, and the thickness is 0.05mm-0.4mm. The above metal meshes all have good electrical conductivity and support, and the prepared self-powered polylactic acid composite fiber membrane has long-term filtration performance.

[0060] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0061] Example 1

[0062] An embodiment of the polylactic acid composite fiber membrane of the present invention, the preparation process of the polylactic acid composite fiber membrane of this embodiment is as follows Figure 1 As shown, the preparation method comprises:

[0063] Step S1. Preparation of nano-barium titanate: 6.35 g of barium hydroxide was dissolved in 200 mL of deionized water, and then 1 g of polyvinyl pyrrolidone was added thereto. After the mixture was completely dissolved by stirring, 3.18 g of titanium tetrachloride was slowly added thereto. After stirring evenly, 1.06 g of potassium hydroxide was added thereto to adjust the pH value. After the mixture was evenly dissolved, it was transferred to a polytetrafluoroethylene reactor and subjected to microwave-assisted hydrothermal synthesis reaction at 90° C. and 400 W power for 4 h. The obtained product was then washed with deionized water, filtered, and placed in a constant temperature drying oven to obtain nano-barium titanate.

[0064] Step S2. Preparation of tetragonal barium titanate crystals: calcining the nano-barium titanate obtained in step S1 at 800° C. for 8 h to obtain tetragonal barium titanate crystals, the purity of which is 99.8%;

[0065] Step S3. Preparation of polylactic acid composite fiber membrane: prepare 10mL of a mixed solvent with a volume ratio of 3:7 of N,N-dimethylformamide and dichloromethane, and add 1g of polylactic acid, 0.5g of tetragonal barium titanate crystals and 0.1g of polyvinyl pyrrolidone, mix them completely and disperse them evenly to obtain a spinning solution; and take 2mL of the spinning solution and pass it through an electrospinning machine under the parameters of an output voltage of 30kV, a flow rate of 1mL / h, a spinning collector rotation speed of 800rpm, a spinning temperature of 23°C, and a spinning distance of 10cm to obtain a polylactic acid composite fiber membrane.

[0066] Example 2

[0067] An embodiment of the polylactic acid composite fiber membrane of the present invention, the preparation method of the polylactic acid composite fiber membrane of this embodiment comprises:

[0068] Step S1. Preparation of nano-barium titanate: 8 g of barium chloride is dissolved in 200 mL of deionized water, and then 8 g of polyvinyl pyrrolidone is added thereto. After the mixture is completely dissolved by stirring, 8 g of titanium dioxide is slowly added thereto. After stirring evenly, 2 g of potassium hydroxide is added to adjust the pH value. After the mixture is evenly dissolved, the mixture is transferred to a polytetrafluoroethylene reactor and subjected to microwave-assisted hydrothermal synthesis reaction at 160° C. and 800 W power for 5 h. The obtained product is then washed with deionized water, filtered, and placed in a constant temperature drying oven to obtain nano-barium titanate.

[0069] Step S2. Preparation of tetragonal barium titanate crystals: calcining the nano-barium titanate obtained in step S1 at 1200° C. for 3 h to obtain tetragonal barium titanate crystals, the purity of which is 99.7%;

[0070] Step S3. Preparation of polylactic acid composite fiber membrane: prepare 10mL of a mixed solvent of N,N-dimethylformamide and chloroform in a volume ratio of 2:3, and add 2g of polylactic acid, 0.8g of tetragonal barium titanate crystals and 0.3g of dopamine hydrochloride, mix them completely and disperse them evenly to obtain a spinning solution; and take 1mL of the spinning solution and pass it through an electrospinning machine under the parameters of an output voltage of 30kV, a flow rate of 0.8mL / h, a spinning collector rotation speed of 1000rpm, a spinning temperature of 25°C, and a spinning distance of 10cm to obtain a polylactic acid composite fiber membrane.

[0071] Example 3

[0072] An embodiment of the polylactic acid composite fiber membrane of the present invention, the preparation method of the polylactic acid composite fiber membrane of this embodiment comprises:

[0073] Step S1. Preparation of nano-barium titanate: 9 g of barium hydroxide was dissolved in 200 mL of deionized water, and then 2 g of carboxymethyl cellulose was added thereto. After being completely dissolved by stirring, 8 g of titanium dioxide was slowly added thereto. After being stirred evenly, 18 g of ammonia water was added to adjust the pH value. After being evenly dissolved, it was transferred to a polytetrafluoroethylene reactor and subjected to microwave-assisted hydrothermal synthesis reaction at 180° C. and 300 W power for 1 h. The obtained product was then washed with deionized water, filtered, and placed in a constant temperature drying oven to obtain nano-barium titanate.

[0074] Step S2. Preparation of tetragonal barium titanate crystals: calcining the nano-barium titanate obtained in step S1 at 1200° C. for 8 h to obtain tetragonal barium titanate crystals, the purity of which is 99.8%;

[0075] Step S3. Preparation of polylactic acid composite fiber membrane: using 10 mL of dichloromethane as solvent, add 1 g of polylactic acid, 2 g of tetragonal barium titanate crystals and 2 g of polyvinyl pyrrolidone, mix them completely and disperse them evenly to obtain a spinning solution; and take 2 mL of the spinning solution and pass it through an electrospinning machine under the following parameters: output voltage of 15 kV, flow rate of 1.5 mL / h, spinning collector rotation speed of 300 rpm, spinning temperature of 50°C, and spinning distance of 10 cm to obtain a polylactic acid composite fiber membrane.

[0076] Example 4

[0077] An embodiment of the polylactic acid composite fiber membrane of the present invention, the preparation method of the polylactic acid composite fiber membrane of this embodiment comprises:

[0078] Step S1. Preparation of nano-barium titanate: 8 g of barium acetate was dissolved in 200 mL of deionized water, and then 0.5 g of polyvinyl pyrrolidone and 0.5 g of dopamine hydrochloride were added thereto, and after being completely dissolved by stirring, 10 g of titanium tetrachloride and 6 g of titanium dioxide were slowly added thereto, and 4 g of sodium hydroxide was added thereto to adjust the pH value after stirring evenly. After being evenly dissolved, the mixture was transferred to a polytetrafluoroethylene reactor, and subjected to microwave-assisted hydrothermal synthesis reaction at 90° C. and 500 W power for 4 h. The obtained product was then washed with deionized water, filtered, and placed in a constant temperature drying oven to obtain nano-barium titanate;

[0079] Step S2. Preparation of tetragonal barium titanate crystals: calcining the nano-barium titanate obtained in step S1 at 1000° C. for 5 h to obtain tetragonal barium titanate crystals with a purity of 99.9%;

[0080] Step S3. Preparation of polylactic acid composite fiber membrane: using 10 mL of N,N-dimethylformamide as solvent, add 0.55 g of polylactic acid, 0.11 g of tetragonal barium titanate crystals and 0.25 g of polyvinyl pyrrolidone, and mix and disperse them completely to obtain a spinning solution; and take 3.64 mL of the spinning solution and pass it through an electrospinning machine under the conditions of an output voltage of 50 kV, a flow rate of 0.5 mL / h, a spinning collector rotation speed of 2500 rpm, a spinning temperature of 10°C, and a spinning distance of 10 cm to obtain a polylactic acid composite fiber membrane.

[0081] Embodiment 5-7

[0082] The embodiment of the polylactic acid composite fiber membrane of the present invention, the difference between the preparation method of the polylactic acid composite fiber membrane of embodiments 5-7 and embodiment 1 is that the calcination conditions of the nano-barium titanate in step S2 are different, and the electrostatic spinning conditions in step S3 are different. Among them, the calcination temperature of embodiment 5 is 1100℃, the calcination time is 7h, and the fiber winding speed during electrostatic spinning is 2500rpm; the calcination temperature of embodiment 6 is 900℃, the calcination time is 4h, and the fiber winding speed during electrostatic spinning is 700rpm; the calcination temperature of embodiment 7 is 800℃, the calcination time is 4h, and the fiber winding speed during electrostatic spinning is 300rpm.

[0083] Embodiment 8-10

[0084] The embodiment of the polylactic acid composite fiber membrane of the present invention, the preparation method of the polylactic acid composite fiber membrane of embodiments 8-10 is different from that of embodiment 1 only in that, in step S3, the mass of the tetragonal barium titanate crystals is different. Among them, the mass of the tetragonal barium titanate crystals in embodiment 8 is 2g; the mass of the tetragonal barium titanate crystals in embodiment 9 is 1g; the mass of the tetragonal barium titanate crystals in embodiment 10 is 5g.

[0085] Comparative Example 1

[0086] A polylactic acid composite fiber membrane. The preparation method of the polylactic acid composite fiber membrane is different from that of Example 2 only in that step S2 is omitted, and the nano barium titanate prepared in step S1 is used to replace the tetragonal barium titanate crystals to prepare the polylactic acid composite fiber membrane.

[0087] Comparative Example 2

[0088] A polylactic acid fiber membrane. The preparation method of the polylactic acid fiber membrane is different from that of Example 3 in that no tetragonal barium titanate crystals are added.

[0089] Comparative Example 3

[0090] A polylactic acid composite fiber membrane. The preparation method of the polylactic acid composite fiber membrane is different from that of Example 1 only in that the calcination conditions of nano-barium titanate in step S2 are different, specifically: the calcination temperature is 1500° C., and the calcination time is 9 hours.

[0091] Comparative Example 4

[0092] A polylactic acid composite fiber membrane. The preparation method of the polylactic acid composite fiber membrane is different from that of Example 1 only in that the electrospinning conditions in step S3 are different, specifically: the fiber winding speed during electrospinning is 10 rpm.

[0093] Examples 11-20

[0094] The embodiment of the self-powered polylactic acid composite fiber membrane of the present invention has a preparation flow chart as shown in Figure 1 As shown, Examples 12-22 are respectively composed of the polylactic acid composite fiber membrane of Examples 1-11 and a metal mesh, wherein the metal mesh is a copper mesh with an aperture of 80 mesh, a wire diameter of 0.1 mm, a thickness of 0.2 mm, and is assembled on one side.

[0095] Comparative Examples 5-8

[0096] Comparative Examples 5, 7, and 8 are self-powered polylactic acid composite fiber membranes, and Comparative Example 6 is a self-powered polylactic acid fiber membrane. Comparative Examples 5-8 are respectively composed of the polylactic acid composite fiber membranes of Comparative Examples 1-4 or polylactic acid fiber membranes and a metal mesh. The metal mesh is a copper mesh with an aperture of 80 mesh, a wire diameter of 0.1 mm, a thickness of 0.2 mm, and is assembled on one side.

[0097] Performance Testing

[0098] 1. Microstructure: The microstructure of nano-barium titanate, tetragonal barium titanate crystals and polylactic acid composite fiber membrane was observed by field emission scanning electron microscope (model JSM-7900F, Japan Electronics). The size of tetragonal barium titanate crystals and the diameter of polylactic acid fiber were counted and calculated by ImageJ software.

[0099] 2. Mechanical properties test: After cutting the polylactic acid composite fiber film or polylactic acid fiber film, tensile specimens were obtained. According to the ASTM D638-2003 plastic tensile properties test standard of the American Society for Testing and Materials, a universal tensile machine (model 4403, sensor 100N) of Instron Company of the United States was used to test the tensile properties. At least 3 parallel test samples were guaranteed for each group, and the results were averaged.

[0100] 3. Surface potential test: A non-contact electrostatic meter (VM54XQS, Quatek, USA) was used to test the surface potential of the self-powered polylactic acid composite fiber membrane or the self-powered fiber membrane. The test height was 2 cm, the temperature and humidity were constant at 25°C and 45%, and 20 data points were randomly collected for each sample and the average value was taken.

[0101] 4. Relative dielectric constant test: The relative dielectric constant of the polylactic acid composite fiber membrane was tested by a dielectric constant tester (model WK-6500B, Wayne Kerr Company, UK).

[0102] 5. Filtration performance test: The air filtration performance of the self-powered polylactic acid composite fiber membrane or the self-powered fiber membrane (area 113.04 cm2) was tested using the LZC-K automatic filter material tester (Suzhou Huada Instrument Equipment Co., Ltd.), the gas flow rate was set to 65 L / min, and the particle size range of the NaCl atomized particles generated by the aerosol generator was 0.1-10 μm. Three different positions were tested in each group, and the results were averaged.

[0103] The performance test results of Examples 1-11 and Comparative Examples 1-4 are shown in Table 1, and the performance test results of Examples 12-22 and Comparative Examples 5-8 are shown in Table 2.

[0104] Table 1

[0105]

[0106] Table 2

[0107]

[0108]

[0109] Figure 2 This is a scanning electron microscope image of the tetragonal barium titanate crystals described in Example 1. It can be seen from the image that the structure of the tetragonal barium titanate crystals generated by microwave-assisted hydrothermal synthesis and high-temperature calcination is uniform and complete. Figure 3 This is a scanning electron microscope image of the polylactic acid fiber in the polylactic acid composite fiber membrane described in Example 2. It can be seen from the figure that the tetragonal barium titanate crystals are well embedded in the fibers, and the structure between the fibers is more compact, with a small risk of falling off under external force. In addition, experiments have found that under the same conditions, after adding tetragonal barium titanate crystals, the diameter of the fiber becomes thinner and the pores increase, which is more conducive to blocking fine particles.

[0110] Table 1 shows the performance test results of Examples 1-10 and Comparative Examples 1-4. It can be seen from the table that Examples 1-10 all have good mechanical properties and can meet the mechanical performance requirements of the polylactic acid composite fiber membrane in the field of air filtration. In addition, the polylactic acid composite fiber membrane described in Examples 1-10 also has a relatively high dielectric constant, which is suitable for filtering fine particulate matter. Comparative Example 1 did not calcine the nano-barium titanate, and the nano-barium titanate embedded in the polylactic acid fiber was cubic phase barium titanate, which had a low dielectric constant. Comparative Example 2 did not add tetragonal phase barium titanate crystals, and its dielectric constant was extremely low. The size of the tetragonal phase barium titanate crystals in Comparative Example 3 is not within the range of 20nm-100nm, and the average diameter of the polylactic acid fiber in Comparative Example 4 is not within the range of 100nm-800nm. The mechanical properties and dielectric properties of the polylactic acid composite fiber membrane cannot be balanced, and its practicality is poor.

[0111] Table 2 shows the performance test results of Examples 11-20 and Comparative Examples 5-8, and their surface potential and filtration efficiency match the dielectric constants of Examples 1-10 and Comparative Examples 1-4, respectively. Through the filtration experiment, it was found that the surface potential of the self-powered polylactic acid composite fiber membrane was improved compared with the static state during the filtration experiment, and the surface potential of the self-powered polylactic acid composite fiber membrane described in Examples 11-20 increased significantly. This is mainly due to the addition of high-purity tetragonal barium titanate crystals, which greatly improved the dielectric constant of the fiber membrane, and relied on the ferroelectricity of the tetragonal barium titanate crystals. When subjected to external forces, polarization will occur to form an electric dipole moment, thereby showing polarity at both ends of the fiber membrane, generating polar charges, thereby increasing the surface potential of the fiber membrane.

[0112] By comparing the performance test results of Examples 11-20, it can be found that when the average diameter of the polylactic acid composite fiber membrane is 300nm-500nm and the average particle size of the tetragonal barium titanate crystals is 30nm-50nm, the filtration performance of the self-powered polylactic acid composite fiber membrane is the best.

[0113] This shows that the nano barium titanate prepared by the method of the present invention can form high-yield high-purity tetragonal barium titanate crystals after calcination, and can be spun into a polylactic acid composite fiber membrane after mixing with polylactic acid, a dispersant and a solvent, and can be combined with a metal mesh to form a self-powered polylactic acid composite fiber membrane with good surface properties, high surface potential, high mechanical properties and high filterability, which has broad application prospects.

[0114] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A polylactic acid composite fiber membrane, characterized in that: The polylactic acid composite fiber membrane comprises polylactic acid fibers and tetragonal barium titanate crystals, the average diameter of the polylactic acid fibers is 100nm-800nm, the average particle size of the tetragonal barium titanate crystals is 20nm-100nm, and the tetragonal barium titanate crystals are partially or completely embedded in the polylactic acid fibers.

2. The polylactic acid composite fiber membrane according to claim 1, characterized in that: The average diameter of the polylactic acid fiber is 300nm-500nm, and the average particle size of the tetragonal barium titanate crystal is 30nm-50nm.

3. The polylactic acid composite fiber membrane according to claim 1 or 2, characterized in that: The mass ratio of the polylactic acid fiber to the tetragonal barium titanate crystal is 1:5-2:

1.

4. The polylactic acid composite fiber membrane according to claim 3, characterized in that: The mass ratio of the polylactic acid fiber to the tetragonal barium titanate crystal is 1:2-2:

1.

5. A method for preparing a polylactic acid composite fiber membrane according to any one of claims 1 to 4, characterized in that: include: Step S1, preparing nano-barium titanate: adding a barium salt, a titanium-containing compound, and a first dispersant into water to obtain a first mixed solution, adjusting the pH value, and obtaining nano-barium titanate through a hydrothermal synthesis reaction; Step S2, preparing tetragonal barium titanate crystals: calcining the nano-barium titanate to obtain tetragonal barium titanate crystals; Step S3, preparing a polylactic acid composite fiber membrane: adding the tetragonal barium titanate crystals, polylactic acid and a second dispersant into a solvent to obtain a second mixed solution, obtaining a spinning solution, and preparing the polylactic acid composite fiber membrane by electrospinning.

6. The preparation method according to claim 5, characterized in that: In the step S1, The barium salt is at least one of barium hydroxide, barium chloride and barium acetate; and / or The titanium-containing compound is at least one of titanium dioxide and titanium tetrachloride; and / or The first dispersant is at least one of polyvinyl pyrrolidone, carboxymethyl cellulose and dopamine hydrochloride; and / or In the step of adjusting the pH value, the pH value of the first mixed solution is controlled to be 9-14; a pH adjuster is used to adjust the pH value, and the pH adjuster is at least one of potassium hydroxide, sodium hydroxide, and ammonia water; and / or Based on the total mass of the first mixed liquid, the mass fraction of the barium salt is 3wt%-8wt%, the mass ratio of the titanium-containing compound to the barium salt is 1:2-2:1, the mass ratio of the first dispersant to the barium salt is 1:8-1:1, and the mass ratio of the pH adjuster to the barium salt is 1:6-2:

1.

7. The preparation method according to claim 5, characterized in that: In the step S3, The solvent is at least one of N,N-dimethylformamide, dichloromethane and chloroform; and / or The second dispersant is at least one of polyvinyl pyrrolidone and dopamine hydrochloride; and / or Based on the total mass of the second mixed liquid, the mass fraction of the polylactic acid is 5wt%-20wt%, the mass ratio of the tetragonal barium titanate crystals to the polylactic acid is 1:5-2:1, and the mass ratio of the second dispersant to the polylactic acid is 1:10-2:

1.

8. The preparation method according to claim 5, characterized in that: In the step S1, the hydrothermal synthesis reaction is a microwave-assisted hydrothermal synthesis reaction; the temperature of the microwave-assisted hydrothermal synthesis reaction is 90° C.-180° C., the time is 1 h-5 h, and the microwave power is 300 W-1000 W; and / or In the step S2, the calcination temperature is 800°C-1200°C, and the calcination time is 3h-8h; the purity of the tetragonal barium titanate crystals is 99.7%-99.9%, and the average particle size of the tetragonal barium titanate crystals is 20nm-100nm; and / or In step S3, the electrospinning conditions are: output voltage 15kV-50kV, solution consumption rate 0.5mL / h-1.5mL / h, fiber winding speed: 300rpm-2500rpm, spinning temperature 10℃-50℃, spinning distance 8cm-25cm.

9. Use of the polylactic acid composite fiber membrane according to any one of claims 1 to 4 in the field of preparing materials for filtering fine particles.

10. A self-powered polylactic acid composite fiber membrane, characterized in that: It comprises the polylactic acid composite fiber membrane described in any one of claims 1 to 4 or the polylactic acid composite fiber membrane prepared by the preparation method described in any one of claims 5 to 9, and a metal mesh assembled on one or both sides of the polylactic acid composite fiber membrane; preferably, the metal mesh is one of copper mesh, iron mesh, silver mesh, nickel mesh, titanium mesh, tungsten mesh, and molybdenum mesh; the pore size of the metal mesh is 50-300 mesh, the wire diameter is 0.03mm-0.15mm, and the thickness is 0.05mm-0.4mm.

Citation Information

Patent Citations

  • Piezoelectric stent composition capable of realizing self-generating electricity stimulation as well as preparation method and application thereof

    CN110882420A

  • Tetragonal-phase nano barium titanate powder as well as preparation method and application thereof

    CN116639972A

  • Composite piezoelectric film for sewage treatment and preparation method and application thereof

    CN116726727A

  • Barium titanate fine particle, dispersoid containing the same, and production method thereof

    JP2015067518A

  • Apparatus for connecting reinforcing bars

    KR1020210138988A